2012
DOI: 10.1007/s10847-012-0168-y
|View full text |Cite
|
Sign up to set email alerts
|

A new inclusion complex of amlodipine besylate and soluble β-cyclodextrin polymer: preparation, characterization and dissolution profile

Abstract: Amlodipine besylate (AML) has become the most popular blood pressure medication for hypertensive pets. It belongs to the class I (high solubility and high permeability) according to BCS and is marketed in Europe only as white tablets equivalent to 2.5, 5.0 and 10.0 mg of amlodipine for oral administration. Unfortunately, oral AML dosage for cats and dogs is in the range 0.1–0.2 and 0.625–0.125 mg/kg/die respectively. Moreover, AML shows a slight solubility in water according to Ph. Eur. 7°. According to these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…CD ICs have been extensively studied using different techniques, including differential scanning calorimetry (DSC). This technique corroborates IC formations by comparing the thermal profiles of the isolated precursors with those of the conjugate systems [6,7,8]. However, thermal studies that provide information on CD IC topotactic processes have not been studied.…”
Section: Introductionmentioning
confidence: 80%
“…CD ICs have been extensively studied using different techniques, including differential scanning calorimetry (DSC). This technique corroborates IC formations by comparing the thermal profiles of the isolated precursors with those of the conjugate systems [6,7,8]. However, thermal studies that provide information on CD IC topotactic processes have not been studied.…”
Section: Introductionmentioning
confidence: 80%
“…Several studies that investigated AML inclusion in different β-CDs cavities had already been performed and published, and they served as starting points for the present study. Lauro et al [ 12 ] proved, with phase solubility studies, that the optimal molar ratio to form a stable complex is 2:1 drug/CD. Meantime, Malakzadeh et al [ 29 ] calculated the formation constant and found that a 1:1 molar ratio leads to the encapsulation of AML in β-CDs.…”
Section: Methodsmentioning
confidence: 99%
“…Two forms of amlodipine are reported: S-enantiomer, which is more active, and R-enantiomer [ 10 , 11 ]. Amlodipine besylate (AML), the besylate salt of amlodipine, has become the most used blood pressure medication [ 12 ] and the most widespread cardiovascular drug [ 13 ]. The different polymorph forms of amlodipine besylate (hydrated or solvated forms) can affect pharmaceutical properties like morphology, stability, solubility, dissolution rate, and also the final performance of solid dosage tablets.…”
Section: Introductionmentioning
confidence: 99%
“…Thermograms were recorded by placing accurately given quantities (1-2 mg weighed with a microbalance MTS Mettler Toledo, OH, USA) of each sample in a 40 μ L aluminium pan which was sealed and pierced. The sample was scanned (10°C/min) between 25 and 350°C [ 27 ]. Melting temperature ( T m ) and heat of fusion (Δ H m ) were measured.…”
Section: Methodsmentioning
confidence: 99%